A Group Intervention for Motivational Deficits: Preliminary Investigation of a Blended Care Approach Using Ambulatory Assessment. Issue 5 (September 2022) - Thonon, Bénédicte; Levaux, Marie-Noëlle; van Aubel, Evelyne; Larøi, Frank
Motivational deficits are an important predictor of functional outcomes in individuals with a serious mental illness such as schizophrenia and mood spectrum disorders. The aim of the present study was to explore the feasibility, acceptability, and preliminary efficacy of a group version of "Switch, " an intervention that targets motivational deficits, enriched with an ecological momentary intervention (EMI) approach (i.e., prompts on the participants' smartphone to encourage the use of trained strategies in their daily life). Eight participants with schizophrenia, schizoaffective, or major depressive disorder entered the study. The intervention took place twice a week for 2 months. Assessment measures included traditional evaluations of motivational negative symptoms, apathy, quality of life and daily functioning, in addition to ambulatory assessment methods strategies, including the experience sampling method (ESM) to assess motivation and related processes, and actigraphy (daily step-count) to assess participants' activity level. Four participants were considered as non-completers (followed less than 2/3 of the program) and four were considered as completers. Only completers presented a decrease in amotivation/apathy and an improvement in functional outcomes after the intervention and at follow-up. Furthermore, mixed-effects ESM models showed significant interaction effects on multiple processes related to motivation, indicating improvements only in completers: heightened motivation, increased engagement in meaningful and effortful activities, better mood, higher levels of confidence, increased frequency of projection into the future (pleasure anticipation), and of positive reminiscence. This preliminary investigation provides evidence that Switch may be an effective intervention, with specific effects on motivation and associated processes.